UJI BEDA RATA-RATA DAYA TAHAN TERHADAP RISIKO KRISIS PERBANKAN SEMBILAN BANK UMUM TERBESAR DI INDONESIA PERIODE 2021-2022 - R. Deden Adhianto (POLITEKNIK PIKSI GANESHA, 2023)
This study aims to determine whether there are differences in the resilience of the nine largest banks in Indonesia to the risk of a banking crisis. The sample used is based on purposive sampling of CAR, TPF, Credit, LDR and NPL (Net) performance data for 2021 and 2022 from the nine largest banks in Indonesia. To find out the results, a mean difference test was carried out with the Paired Sample Test or with the Wilcoxon test on the data. The results of the study show that in 2021 and 2022 there is no significant difference in KPMM performance and the value is relatively higher than the BI standard. In the TPF performance test, there were significant differences and the numbers increased. The test results on credit performance show significant differences and the numbers have increased. As for LDR performance, there is no significant difference and is at a ratio level in accordance with BI regulations. In NPL (Net) performance, there is a significant difference with very healthy conditions where the NPL (Net) level is decreasing. Keywords : CAR, DPK, Credit, LDR and NPL (Net)